KUALITAS LAYANAN ONLINE TERHADAP KEPUASAN DAN LOYALITAS PENGGUNA KERETA API EKONOMI MAHARANI SURABAYA PASAR TURI – SEMARANG PONCOL PADA PT. KAI DAOP VIII SURABAYA - Rizal Muttaqin; Didin Fatihudin; Ratri Amelia Aisyah (BALANCE: Economic, Business, Management and Accounting Journal, 2016)
ABSTRACT  The intense competition and the rapid development of technology and information asserteda better system, fast and reliable in solving the problem, especially in the transportation services sector. Consumer decision in determining and selecting the public transportation depended on many things including online service quality factors.This study aim to assess and analyzed the effect of online service quality on satisfaction and loyalty of Maharani economic railway user at Railway Company operational area VIII Surabaya PasarTuri. The model used in this research approach was causality with descriptive research methods.The population in this study was the Maharani Railway passengers with departure from Pasar Turi Surabaya station and destination Poncol Semarang station and vice versa or round-trip (PP). The selected sampleswere 200 respondents. Sample decision technique used Purposive sampling. The data analysis method used Structural Equation Modeling (SEM) with AMOS program. The results of this study showed that: 1) the online service quality has a significant effect to passenger satisfaction. 2) The online service quality has no significant effect to passenger loyalty. 3) The satisfaction has significant effect to passenger loyalty. 4) The online service quality has a significant effect to the passenger’s loyalty which is mediated by the passenger’s satisfaction.Keywords : Quality, Online Services, Satisfaction, Loyalty.Correspondence to : lazir.think@gmail.com, dienafdloka@gmail.com, reetrayy@gmail.com